Pattern of antidiabetic drugs use in type-2 diabetic patients in a medicine outpatient clinic of a tertiary care teaching hospital - Patel, Bela; Oza, Bhavit; Patel, Kamlesh P.; Malhotra, Supriya D.; Patel, Varsha J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes mellitus (DM) is an important public health problem in developing countries. Drug utilisation study of antidiabetic agents is of paramount importance to promote rational drug use in diabetics and make available valuable information for the healthcare team. The aim of study was to investigate the drug utilization pattern in type-2 diabetic patients. Methods: A prospective, cross-sectional study was carried out in medicine outpatient clinic of tertiary care hospital, Ahmedabad for eight weeks. Patients with type-2 diabetes and on drug therapy for at least one month were included. Patients’ socio-demographic and clinical data were noted in a pre-designed proforma. Data was analysed by using SPSS version 20 and Excel 2007. Results: Total 114 patients were enrolled with mean (± standard deviation) age and duration of diabetes of 56.8 ± 10.5 and 8.3 ± 9.4 years respectively. Male: Female ratio was 0.72:1. Mean fasting and postprandial blood glucose levels were 147.5 ± 73.1 and 215.6 ± 97.3 mg/dl respectively. Most common symptom was weakness/fatigue (77.2%). Hypertension (70.2%) was most common co-morbid illness. Mean number of drugs prescribed were 7.8 ± 2.5. Total numbers of patients receiving more than five drugs were 89.5%. Most commonly used drug group was biguanides (87.7%) followed by sulphonylureas (68.4%). Conclusion: Metformin (biguanide) was the most utilized (87.7%) antidiabetic drug for type-2 diabetes. This study revealed that the pattern of antidiabetic prescription was rational and largely compliant with NICE (National Institute for Health and Clinical Excellence) guidelines.